Electromagnetic shielding sheet and electromagnetic shielding wiring circuit board
Patent Information
- Application Number
- JP2023203519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2039-11-28
AI Technical Summary
【0010】 本発明によれば、ハンダリフロー耐性に優れ、高周波伝送回路に用いた場合においても伝送損失を低減させ、優れた高周波シールド性を示し、かつ優れた高温高湿安定性と高い打抜き加工性を示す電磁波シールドシート、および電磁波シールド性配線回路基板を提供することができるという優れた効果を奏する。
Smart Images

Figure 0007632575000007 
Figure 0007632575000008 
Figure 0007632575000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic shielding sheet and an electromagnetic shielding wired circuit board, and more particularly to an electromagnetic shielding sheet suitable for use by being joined to a part of a component that emits electromagnetic waves, and an electromagnetic shielding wired circuit board using the electromagnetic shielding sheet. [Background technology]
[0002] Wiring circuit boards such as printed wiring boards are built into various electronic devices including mobile terminals, PCs, servers, etc. These wiring circuit boards are provided with an electromagnetic wave shielding structure to prevent malfunctions due to external magnetic fields and radio waves and to reduce unnecessary radiation from electrical signals.
[0003] As transmission signals become faster, electromagnetic shielding sheets are also required to have electromagnetic shielding properties (hereinafter referred to as high-frequency shielding properties) that can deal with high-frequency noise, and to reduce transmission loss in the high-frequency range (hereinafter sometimes referred to as transmission characteristics). Patent Document 1 discloses a configuration having a metal layer with a thickness of 0.5 to 12 μm and an anisotropic conductive adhesive layer in a laminated state. It is described that this configuration provides good shielding of electric field waves, magnetic field waves, and electromagnetic waves that travel from one side of the electromagnetic shielding sheet to the other side, and reduces transmission loss. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2013 / 077108 [Patent Document 2] JP 2013-168643 A [Patent Document 3] JP 2000-124660 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, in electronic devices such as mobile phones, as the transmission speed of transmission signals increases, the electromagnetic shielding sheets on the wiring circuit boards built into these devices are also required to have high-frequency shielding properties and transmission characteristics. For this reason, Patent Document 1 shows, as an example, that excellent transmission characteristics can be achieved by using a metal layer with a thickness of 0.5 to 12 μm. In addition, when an electromagnetic wave shielding wired circuit board in which an electromagnetic wave shielding sheet using a metal layer is attached to the wired circuit board is subjected to a heat treatment such as solder reflow, there is a problem that floating occurs between the layers due to volatile components generated from inside the wired circuit board, and foaming or the like causes a poor appearance and poor connection (hereinafter, this may be referred to as solder reflow resistance).To address this problem, for example, Patent Document 2 uses a metal foil having a plurality of pinholes in the metal thin film layer, and allows the volatile components to permeate through the pinholes in the metal thin film layer, thereby suppressing floating and foaming between the layers.
[0006] Furthermore, when mounting the electromagnetic shielding sheet on a wiring circuit board, the large-area electromagnetic shielding sheet is processed into small pieces that match the shape of the wiring circuit board to which it is to be attached. From the viewpoint of production efficiency, the mainstream method of processing into small pieces is "punching", in which a "punching blade" having a predetermined shape is inserted perpendicularly into a large-area electromagnetic shielding sheet. In punching, the punching blade comes into contact with the conductive adhesive layer during punch cutting, and there have been problems in that the soft conductive adhesive layer adheres to the punching blade, deteriorating the sharpness of the blade, or that the attached conductive adhesive layer stretches and protrudes from the small pieces, damaging the aesthetic appearance. (Hereinafter referred to as "punching processability") In Patent Document 3, an electromagnetic shielding sheet is provided with a metal-coated fiber base fabric, which improves processability against cutting. However, in this invention, since the part that acts as an electromagnetic shield is the fiber base fabric, sufficient electromagnetic shielding properties cannot be achieved against high-frequency, short-period noise.
[0007] Meanwhile, with the recent worldwide spread of electronic devices such as smartphones and tablet terminals, reliability under all temperature and humidity conditions is required. When the wiring circuit boards equipped with the electromagnetic shielding sheets of Patent Document 1 and Patent Document 2 are exposed to a high-temperature, high-humidity environment, water absorption occurs due to softening of the electromagnetic shielding sheet, causing problems such as deterioration due to hydrolysis and loss of conductivity due to swelling, resulting in disconnection of the connection with the ground circuit (hereinafter referred to as high-temperature, high-humidity stability).
[0008] The present invention has been made in consideration of the above-mentioned background, and an object of the present invention is to provide an electromagnetic wave shielding sheet that has solder reflow resistance, excellent high-temperature and high-humidity stability, and high punching workability, as well as excellent high-frequency shielding properties and transmission characteristics suitable for high-frequency signals, and a wiring circuit board that uses the electromagnetic wave shielding sheet. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that the problems of the present invention can be solved in the following aspect, and have completed the present invention. That is, the electromagnetic wave shielding sheet of the present invention has a laminate having a conductive adhesive layer, a metal layer, and a protective layer in this order, the conductive adhesive layer contains a binder resin, a conductive filler, and reinforcing particles, and the reinforcing particles have a DBP oil absorption of 15 to 400 ml / 100 g as defined in JIS K 6217-4. Effect of the Invention
[0010] The present invention has the excellent effect of providing an electromagnetic shielding sheet and an electromagnetic shielding wiring circuit board that have excellent solder reflow resistance, reduce transmission loss even when used in a high-frequency transmission circuit, exhibit excellent high-frequency shielding properties, and also exhibit excellent high-temperature and high-humidity stability and high punching workability. [Brief description of the drawings]
[0011] [Figure 1]1 is a cross-sectional view illustrating an electromagnetic wave shielding sheet according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an aggregate of reinforcing particles. [Diagram 3] 1 is a schematic cross-sectional view of a cut portion showing an example of an electromagnetic wave shielding printed circuit board according to an embodiment of the present invention; [Figure 4] 1A and 1B are schematic plan views of the principal surface side of wiring boards having coplanar circuits according to examples and comparative examples. [Diagram 5] 1A and 1B are schematic plan views of the rear surface side of wiring boards having coplanar circuits according to examples and comparative examples. [Figure 6] 1A and 1B are schematic plan views of the principal surface side of wiring boards having coplanar circuits with electromagnetic shielding sheets according to examples and comparative examples. [Figure 7] FIG. 2 is a schematic plan view of a high-temperature and high-humidity stability evaluation and a cross-sectional view of a cut portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] An example of an embodiment to which the present invention is applied will be described below. Note that the size and ratio of each member in the following drawings are for the convenience of explanation and are not limited thereto. Furthermore, in this specification, the expression "any number A to any number B" includes the number A as the lower limit and the number B as the upper limit in the range. Furthermore, in this specification, the term "sheet" includes not only "sheet" as defined by JIS, but also "film". Furthermore, in this specification, The numerical values specified in are values determined by the methods disclosed in the embodiments or examples.
[0013] <Electromagnetic wave shielding sheet> The electromagnetic shielding sheet of the present invention has a laminate including at least a conductive adhesive layer, a metal layer, and a protective layer in this order. Fig. 1 is a cross-sectional view illustrating an electromagnetic shielding sheet 10 according to an embodiment of the present invention. As shown in Fig. 1, the electromagnetic shielding sheet 10 has a laminate including a conductive adhesive layer 1, a metal layer 2, and a protective layer 3 in this order, and the metal layer 2 is disposed between the conductive adhesive layer 1 and the protective layer 3. The electromagnetic shielding sheet 10 is produced, for example, by bonding the surface of the conductive adhesive layer 1 side to a wired circuit board, which is an adherend, to form an electromagnetic shielding layer, thereby producing an electromagnetic shielding wired circuit board. That is, of the surface of the metal layer 2, the surface that faces the signal wiring in the wired circuit board is the surface that is in close contact with the conductive adhesive layer 1.
[0014] Conductive adhesive layer The conductive adhesive layer can be formed using a conductive resin composition. The conductive resin composition includes a binder resin, a conductive filler, and reinforcing particles. The binder resin is preferably a thermoplastic resin, or a thermosetting resin and a curing agent. The conductive adhesive layer can be either an isotropic conductive adhesive layer or an anisotropic conductive adhesive layer. The isotropic conductive adhesive layer has conductivity in the vertical and horizontal directions when the electromagnetic shielding sheet is placed horizontally. The anisotropic conductive adhesive layer has conductivity only in the vertical direction when the electromagnetic shielding sheet is placed horizontally. The conductive adhesive layer may be either isotropically conductive or anisotropically conductive, and anisotropically conductive is preferred since it allows for cost reduction.
[0015] [Reinforcing particles] The conductive adhesive layer contains reinforcing particles having a DBP oil absorption of 15 to 400 ml / 100 g as specified by JIS K 6217-4. In this specification, the reinforcing particles refer to particles that have the effect of improving the strength of the conductive adhesive layer when added to the conductive adhesive layer. When the conductive adhesive layer contains reinforcing particles having a DBP oil absorption of 15 to 400 ml / 100 g, the punching processability can be improved. The improvement in punching processability is presumed to occur due to an estimated action described below, but the mechanism of action of the effect of the present invention is not limited to this estimated action.
[0016] DBP oil absorption refers to the amount of DBP (dibutyl phthalate) that a target substance can absorb, and can be used as an index for understanding the degree of development of aggregates (hereinafter referred to as "structure") of reinforcing particles, which will be described later.
[0017] The reinforcing particles contained in the conductive adhesive layer of the present invention form secondary particle-like aggregates (hereinafter, aggregates) by aggregation, bonding, or fusion of the base fine particles (hereinafter, primary particles). Figure 2 shows an aggregate of reinforcing particles. As shown in Figure 2, the structure represents the degree of development of the aggregate.
[0018] (estimated effect) The contribution of the reinforcing particles to improving the strength of the conductive adhesive layer is estimated below. The primary particles of the reinforcing particles have the property of gathering together due to multiple interparticle interactions such as electrostatic interactions, and multiple primary particles coagulate, bond, or fuse to form aggregates. When the primary particles aggregate, they are not necessarily closest packed, and spaces are generated in the aggregate. When reinforcing particles are immersed in a liquid such as oil or resin solution, the low or high molecular weight molecules in the liquid are The molecules enter the space in the aggregate. If it is a polymer that enters the space, not the entire molecular chain of the polymer enters the space, but only a part of the molecular chain. When the above phenomenon occurs at multiple ends of the polymer, a state is formed in which multiple reinforcing particles are connected by polymer chains. When the above phenomenon occurs in large numbers in the composition, a pseudo-crosslinked structure is formed, leading to improved strength of the composition.
[0019] This presumed effect is influenced by the size of the voids in the aggregates and the extent of the structure. That is, the longer the structure, the more difficult it is for the primary particles to aggregate in close packing, and the larger the voids are formed or the more voids are formed. As a result, the reinforcing particles form a denser pseudo-crosslinked structure, and the composition obtains higher strength.
[0020] DBP oil absorption is used as an index to measure the size of the space. DBP oil absorption is positively correlated with the amount of DBP (dibutyl phthalate) that the target substance can absorb, i.e., the total volume of space in the aggregate. The higher the DBP oil absorption, the longer the structure will be, the wider and more the space in the aggregate will be, and the higher the density of the pseudo-crosslinked structure will be formed in the composition. The above is the presumed function of the reinforcing particles in improving the strength of the conductive adhesive layer, however, the mechanism of action of the effect of the present invention is not limited to this presumed function.
[0021] The reinforcing particles used in the present invention have a DBP oil absorption of 15 to 400 ml / 100 g as specified by JIS K 6217-4. When the DBP oil absorption of the reinforcing particles is 15 ml / 100 g or more, the structure can be made sufficiently long, and a sufficient pseudo-crosslinking effect occurs. As a result, when the electromagnetic shielding sheet is punched, sagging of the conductive adhesive layer can be suppressed. In addition, when the DBP oil absorption of the reinforcing particles is 400 ml / 100 g or less, a large amount of resin is prevented from being taken in by the reinforcing particles, the occurrence of a region in which the resin is insufficient in the conductive adhesive layer is suppressed, and the occurrence of defective appearance such as cracks and blistering of the electromagnetic shielding layer originating from the defect during solder reflow resistance evaluation can be suppressed. The DBP oil absorption of the reinforcing particles is more preferably 30 to 350 ml / 100 g, and even more preferably 50 to 250 ml / 100 g.
[0022] The reinforcing particle content in 100% by mass of the conductive adhesive layer is preferably 1 to 20% by mass. When the reinforcing particle content is 1% by mass or more, a sufficient pseudo-crosslinking effect can be generated in the conductive adhesive layer, and high-temperature and high-humidity stability and punching workability are further improved. When the reinforcing particle content is 20% by mass or less, a large amount of resin is prevented from being taken up by the reinforcing particles, the occurrence of regions in the conductive adhesive layer where there is insufficient resin is suppressed, and solder reflow resistance and punching workability are further improved. It is more preferable that the reinforcing particle content in the conductive adhesive layer is 5 to 7% by mass.
[0023] The content of the reinforcing particles in the conductive adhesive layer relative to 100 parts by mass of the conductive filler is preferably 1 to 60 parts by mass, more preferably 2 to 55 parts by mass, and particularly preferably 7 to 15 parts by mass. By being in this range, it is possible to obtain an excellent balance between high temperature and high humidity stability, transmission characteristics, and high frequency shielding properties.
[0024] The reinforcing particle / conductive filler mass ratio in the conductive adhesive layer is preferably 1 / 75 to 2 / 3. When the reinforcing particle / conductive filler mass ratio is 1 / 75 or more, punching workability and high temperature and high humidity stability are further improved, and when it is 2 / 3 or less, reflowability is improved. The reinforcing particle / conductive filler mass ratio in the conductive adhesive layer is more preferably 1 / 36 to 2 / 3, and particularly preferably 1 / 14 to 1 / 6.
[0025] Examples of reinforcing particles are not limited as long as they have the effect of improving the strength of the conductive adhesive layer, and include carbon-based particles such as carbon black, carbon nanotubes, graphite, carbon fibers, and carbon nanoplates, or the like, as described in JP 2018 / 185938 A. Examples of the inorganic particles include trilithium phosphate (Li3PO4) described in the publication and inorganic particles such as silica described in International Publication No. 2016 / 021467. Any known particles can be used as long as they have aggregation and the DBP oil absorption can be measured. Among them, it is preferable to use carbon black. Carbon black may include those that are classified in a specific way, such as Ketjen black and acetylene black, and those that are not classified in a specific way as described above. These reinforcing particles do not cause entangled self-aggregation like fibrous carbon nanotubes, and have functional groups on the surface, which causes excessive self-aggregation between aggregates of silica and the like, and therefore cause strong interactions with the resin without causing such self-aggregation, making them uniformly dispersed in the conductive adhesive layer and suppressing the occurrence of foaming points during solder reflow, which is preferable.
[0026] When the primary particles are spherical, ellipsoidal, or amorphous, the average primary particle diameter of the reinforcing particles is preferably 30 nm or less from the viewpoint of improving punching processability. When the primary particles are fibrous, it is preferably (fiber length / fiber diameter)≦10 ... By having (fiber length / fiber diameter)≦100, excessive entanglement between primary particles can be suppressed, the interaction with the resin can be optimized, and punching processability can be improved.
[0027] The reinforcing particles can be produced by any known method, such as a furnace method, an acetylene method, a gasification method, an arc discharge method, a laser evaporation method, a CVD method, a wet method, a dry method, or the like, as long as it is capable of producing particles having the desired DBP oil absorption.
[0028] It is known that the strengths and weaknesses of the structure depend on the type of reinforcing particles, the particle size of the primary particles, and the manufacturing method, but as long as an aggregate with the desired structure can be formed, there are no limitations on the type of reinforcing particles, the particle size of the primary particles, or the manufacturing method.
[0029] [Conductive filler] The conductive filler has a function of imparting electrical conductivity to the conductive adhesive layer. As the material of the conductive filler, for example, conductive metals such as gold, platinum, silver, copper, and nickel, and alloys thereof, as well as fine particles of conductive polymers are preferable, and silver is more preferable in terms of cost and electrical conductivity. The conductive filler has a volume resistivity of 1.0×10 -5 It is preferable to use a material with a volume resistivity of 1.0×10 Ω·cm or less. -5 Materials with a resistance of less than Ω·cm include conductive metals such as gold, platinum, silver, copper, and nickel, as well as alloys thereof, and fine particles of conductive polymers.
[0030] In addition, from the viewpoint of reducing costs, composite microparticles having a core of metal or resin, and a coating layer that coats the surface of the core, are also preferred. Here, the core is preferably appropriately selected from inexpensive nickel, silica, copper and their alloys, and resin. The coating layer is preferably a conductive metal or a conductive polymer. Examples of conductive metals include gold, platinum, silver, nickel, manganese, and indium, as well as alloys thereof. Examples of conductive polymers include polyaniline and polyacetylene. Among these, silver is preferred from the viewpoints of cost and conductivity. The coating layer of the composite particles has a volume resistivity of 1.0×10 -5It is preferable that the material contains a material having a resistivity of Ω·cm or less, and more preferable that the material contains a conductive metal, and particularly preferable that the material contains silver.
[0031] The volume resistivity of a material can be determined by measuring in accordance with JIS C2525.
[0032] The shape of the conductive filler is not limited as long as the desired conductivity can be obtained. Specific examples of the shape include spherical, flake, leaf, dendritic, plate, needle, rod, and grape shapes. It is preferable to mix two kinds of conductive fillers having different shapes. The conductive filler may be used alone or in combination of two or more kinds.
[0033] The average particle size of the conductive filler is D 50 The average particle size is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 7 μm or more, from the viewpoint of ensuring sufficient conductivity. On the other hand, from the viewpoint of achieving compatibility with the thinness of the conductive adhesive layer, it is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. 50 The average particle size can be determined by a laser diffraction / scattering particle size distribution measuring device or the like.
[0034] The conductive filler content in the conductive adhesive layer (100 mass%) is preferably 25 to 90 mass%, more preferably 30 to 70 mass%, and even more preferably 40 to 65 mass%. By making it 25 mass% or more, the connection between the conductive adhesive layer and the ground wiring is improved, so that the high frequency shielding property and the high temperature and high humidity stability are further improved. On the other hand, by making it 90 mass% or less, the solder reflow resistance and the transmission property are further improved.
[0035] [Binder resin] (thermoplastic resin) Examples of thermoplastic resins include polyolefin resins, vinyl resins, styrene-acrylic resins, diene resins, terpene resins, petroleum resins, cellulose resins, polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyimide resins, liquid crystal polymers, fluororesins, etc. Although not particularly limited, from the viewpoint of transmission loss, materials with low dielectric constants and low dielectric dissipation factor are preferred, and from the viewpoint of characteristic impedance, materials with low dielectric constants are preferred, such as liquid crystal polymers and fluororesins. The thermoplastic resins can be used alone or in combination of two or more kinds.
[0036] (thermosetting resin) The thermosetting resin is a resin having a plurality of functional groups capable of reacting with a curing agent. Examples of the functional groups include hydroxyl groups, phenolic hydroxyl groups, methoxymethyl groups, carboxyl groups, amino groups, epoxy groups, oxetanyl groups, oxazoline groups, oxazine groups, aziridine groups, thiol groups, isocyanate groups, blocked isocyanate groups, blocked carboxyl groups, and silanol groups. Examples of the thermosetting resin include known resins such as acrylic resins, maleic acid resins, polybutadiene-based resins, polyester resins, polyurethane resins, polyurethane urea resins, epoxy resins, oxetane resins, phenoxy resins, polyimide resins, polyamide resins, polyamideimide resins, phenolic resins, alkyd resins, amino resins, polylactic acid resins, oxazoline resins, benzoxazine resins, silicone resins, and fluororesins. The thermosetting resins can be used alone or in combination of two or more kinds.
[0037] Among these, polyurethane resin, polyurethane urea resin, polyester resin, epoxy resin, phenoxy resin, polyimide resin, polyamide resin, and polyamideimide resin are preferred from the viewpoint of solder reflow resistance.
[0038] (hardening agent) The curing agent has a plurality of functional groups capable of reacting with the functional groups of the thermosetting resin, and examples of the curing agent include known compounds such as epoxy compounds, acid anhydride group-containing compounds, isocyanate compounds, aziridine compounds, amine compounds, phenol compounds, and organometallic compounds. The curing agent can be used alone or in combination of two or more kinds.
[0039] The curing agent is preferably contained in an amount of 1 to 50 parts by mass, more preferably 3 to 40 parts by mass, and further preferably 3 to 30 parts by mass, based on 100 parts by mass of the thermosetting resin.
[0040] The thermoplastic resin and the thermosetting resin can be used alone or in combination as a mixture of both.
[0041] [Storage modulus of cured conductive adhesive layer] The storage modulus at 85°C of the cured conductive adhesive layer obtained by heating the conductive adhesive layer at 170°C for 30 minutes is 1.0 × 10 6 ~2.0×10 8 The cured conductive adhesive layer preferably has a storage modulus of 1.0×10 Pa at 85° C. 6 ~2.0×10 8 By using a resin having a tensile strength of 100 Pa, the high temperature and high humidity stability is further improved. The cured conductive adhesive layer has a storage modulus of 2.0 × 10 at 85 °C. 7 ~2.0×10 8 Pa, more preferably 5.0×10 7 ~2.0×10 8 Pa is more preferred.
[0042] [Young's modulus of conductive adhesive layer] The Young's modulus of the conductive adhesive layer at 23°C is preferably 10 to 450 MPa. When the Young's modulus of the conductive adhesive layer at 23°C is 10 MPa or more, the conductive adhesive layer is cut without being stretched by the shear stress generated during punching, and punching processability is improved. On the other hand, when the Young's modulus of the conductive adhesive layer at 23°C is 450 MPa or less, the conductive adhesive layer can be given more appropriate flexibility, and cracking of the conductive adhesive layer due to impact during punching can be suppressed. The Young's modulus of the conductive adhesive layer at 23°C is more preferably 50 to 400 MPa, and even more preferably 150 to 350 MPa.
[0043] The conductive resin composition may contain other optional components such as silane coupling agents, rust inhibitors, reducing agents, antioxidants, coloring pigments, dyes, tackifier resins, plasticizers, UV absorbers, defoamers, leveling adjusters, fillers, and flame retardants.
[0044] The coloring pigment is blended into the conductive resin composition to impart, for example, desired brightness or chromaticity to the conductive adhesive layer. For example, titanium black, such as Titan Black 12S (manufactured by Mitsubishi Materials Corporation), or perylene pigments, such as Pigment Black 31 and Pigment Black 32, can be used as the coloring pigment.
[0045] The conductive resin composition can be obtained by mixing and stirring the materials described above. For the stirring, a known stirring device such as a Dispermat or a homogenizer can be used.
[0046] The conductive adhesive layer can be produced by a known method, for example, by applying a conductive resin composition onto a release sheet and drying the same to form a conductive adhesive layer, or by extruding the conductive resin composition into a sheet using an extrusion molding machine such as a T-die.
[0047] The coating method may be a known coating method such as gravure coating, kiss coating, die coating, lip coating, comma coating, blade coating, roll coating, knife coating, spray coating, bar coating, spin coating, or dip coating. A drying step is preferably carried out during coating. For the drying step, a known drying device such as a hot air dryer or an infrared heater may be used.
[0048] The thickness of the conductive adhesive layer before being heat-pressed is preferably 2 to 30 μm, more preferably 3 to 15 μm, and even more preferably 4 to 9 μm. When the thickness is in the range of 2 to 30 μm, high temperature and humidity stability and solder reflow resistance can be improved.
[0049] 《Metal layer》 The metal layer of the present invention has the function of imparting high frequency shielding properties to the electromagnetic wave shielding sheet.
[0050] [Metal layer thickness] The thickness of the metal layer is preferably 0.3 μm or more. By making the thickness of the metal layer 0.3 μm or more, it is possible to suppress the transmission of the wavelength of electromagnetic noise generated from the wiring circuit board, and to exhibit sufficient high-frequency shielding properties. The thickness of the metal layer is more preferably 0.5 μm or more. On the other hand, the thickness of the metal layer is preferably 7 μm or less. By making the thickness of the metal layer 7 μm or less, it is possible to suppress interlayer peeling during solder reflow due to the difference in the expansion coefficient of the metal layer and the conductive adhesive layer with respect to temperature change, and further to further suppress the occurrence of metal layer burrs during punching. The upper limit of the thickness of the metal layer is more preferably 3.5 μm or less.
[0051] [Metal layer components] The metal layer may be, for example, a metal foil, a metal vapor deposition film, or a metal plating film. The metal used for the metal foil is preferably a conductive metal such as aluminum, copper, silver, or gold, and either one kind of metal or an alloy of multiple metals can be used. From the viewpoint of high frequency shielding properties and cost, copper, silver, and aluminum are more preferable, and copper is even more preferable. For copper, for example, rolled copper foil or electrolytic copper foil is preferably used. The metal used for the metal deposition film and metal plating film is preferably one type of conductive metal such as aluminum, copper, silver, gold, etc., or an alloy of multiple metals, and more preferably copper or silver. One or both surfaces of the metal foil, metal deposition film, and metal plating film may be coated with a metal or an organic substance such as a rust inhibitor.
[0052] Opening The metal layer may have a plurality of openings. The openings improve the solder reflow resistance. The openings allow volatile components contained in the polyimide film and coverlay adhesive of the wiring circuit board to escape to the outside when the electromagnetic shielding wiring circuit board is subjected to solder reflow treatment, and can suppress the occurrence of poor appearance due to interfacial peeling between the coverlay adhesive and the electromagnetic shielding sheet.
[0053] The shape of the opening as viewed from the surface of the metal layer can be various shapes as required, such as a perfect circle, an ellipse, a rectangle, a polygon, a star, a trapezoid, a branch, etc. From the viewpoints of manufacturing costs and ensuring the toughness of the metal layer, the shape of the opening is preferably a perfect circle or an ellipse.
[0054] [Aperture ratio of metal layer] The aperture ratio of the metal layer can be calculated by the following formula (2). Formula (2) (Opening rate [%]) = (Area of openings per unit area) / (Area of openings per unit area + Area of non-openings per unit area) x 100
[0055] The aperture ratio of the metal layer is preferably 0.1 to 20%. When the aperture ratio is 0.1% or more, This is preferable because it allows volatile components to escape sufficiently during the under-reflow treatment, and it is possible to suppress the occurrence of poor appearance due to interfacial peeling between the coverlay adhesive and the electromagnetic shielding sheet, as well as a decrease in connection reliability. On the other hand, an aperture ratio of 20% or less is preferable because it reduces the amount of electromagnetic noise passing through the openings and improves the shielding properties. The aperture ratio range that achieves high levels of both solder reflow resistance and high-frequency shielding properties is more preferably 0.3 to 15%, and even more preferably 0.5 to 6.5%.
[0056] The aperture ratio can be measured, for example, by dividing an opening and a non-opening into two parts using an image magnified 500 to 2000 times by a laser microscope and a scanning electron microscope (SEM) perpendicular to the surface direction of the metal layer, and calculating the number of pixels of the divided colors per unit area as the area of each part.
[0057] [Method of manufacturing a metal layer having openings] The method for producing a metal layer having openings can be a conventional method, and includes a method (i) of forming a pattern resist layer on a metal foil and etching the metal foil to form openings; (ii) a method of printing a conductive paste in a predetermined pattern by screen printing; (iii) a method of screen printing an anchor agent in a predetermined pattern and metal plating only on the surface printed with the anchor agent; and (iv) a manufacturing method described in JP 2015-63730 A are applicable. can. That is, a pattern is printed on a support with a water-soluble or solvent-soluble ink, a metal vapor deposition film is formed on the surface, and the pattern is removed. A release layer is formed on the surface and electrolytic plating is performed to obtain a metal layer having an opening with a carrier. Among these, the opening formation method (i) in which a pattern resist layer is formed and a metal foil is etched is preferred because it allows precise control of the shape of the opening. However, other methods may also be used as long as the shape of the opening can be controlled, and the method for producing the metal layer is not limited to the etching method (i).
[0058] 《Protective layer》 The protective layer can be formed using a resin composition. The resin composition contains a binder resin. The binder resin can be either a thermoplastic resin or a thermosetting resin and a hardener.
[0059] The weight average molecular weight of the binder resin is preferably 10,000 or more. When the weight average molecular weight of the thermosetting resin is 10,000 or more, the polymer chains in the protective layer are densely entangled to prevent the inflow of water vapor, thereby improving the high temperature and high humidity stability. The weight average molecular weight of the thermosetting resin is more preferably 30,000 or more, and even more preferably 50,000 or more.
[0060] [Binder resin] (thermoplastic resin) Examples of thermoplastic resins include polyolefin resins, vinyl resins, styrene-acrylic resins, diene resins, terpene resins, petroleum resins, cellulose resins, polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyimide resins, liquid crystal polymers, fluororesins, etc. Although not particularly limited, from the viewpoint of transmission loss, materials with low dielectric constants and low dielectric dissipation factor are preferred, and from the viewpoint of characteristic impedance, materials with low dielectric constants are preferred, such as liquid crystal polymers and fluororesins. The thermoplastic resins can be used alone or in combination of two or more kinds.
[0061] (thermosetting resin) The thermosetting resin is a resin having a plurality of functional groups capable of reacting with a curing agent. Examples of the functional groups include hydroxyl groups, phenolic hydroxyl groups, methoxymethyl groups, carboxyl groups, amino groups, epoxy groups, oxetanyl groups, oxazoline groups, oxazine groups, aziridine groups, thiol groups, isocyanate groups, blocked isocyanate groups, blocked carboxyl groups, and silanol groups. Examples of the thermosetting resin include acrylic resins, maleic acid resins, polybutadiene-based resins, polyester resins, polyurethane resins, polyurethane urea resins, epoxy resins, oxetane resins, phenoxy resins, polyimide resins, polyamide resins, polyamideimide resins, phenolic resins, alkyd resins, amino resins, polylactic acid resins, oxadiene resins, and ethylene glycol resins. Examples of the resin include known resins such as zoline resin, benzoxazine resin, silicone resin, and fluorine resin. The thermosetting resins can be used alone or in combination of two or more kinds.
[0062] Among these, polyurethane resin, polyurethane urea resin, polyester resin, epoxy resin, phenoxy resin, polyimide resin, polyamide resin, and polyamideimide resin are preferred from the viewpoint of solder reflow resistance.
[0063] (hardening agent) The curing agent has a plurality of functional groups capable of reacting with the functional groups of the thermosetting resin, and examples of the curing agent include known compounds such as epoxy compounds, acid anhydride group-containing compounds, isocyanate compounds, aziridine compounds, amine compounds, phenol compounds, and organometallic compounds. The curing agent can be used alone or in combination of two or more kinds.
[0064] The curing agent is preferably contained in an amount of 1 to 50 parts by mass, more preferably 3 to 40 parts by mass, and even more preferably 3 to 30 parts by mass, relative to 100 parts by mass of the thermosetting resin. When the curing agent is contained in this range, the high temperature and high humidity stability can be improved.
[0065] The thermoplastic resin and the thermosetting resin can be used alone or in combination as a mixture of both.
[0066] The resin composition may contain other optional components such as silane coupling agents, rust inhibitors, reducing agents, antioxidants, coloring pigments, dyes, tackifier resins, plasticizers, UV absorbers, defoamers, leveling adjusters, fillers, and flame retardants.
[0067] The resin composition can be obtained by mixing and stirring the materials described above. For the stirring, a known stirring device such as a Dispermat or a homogenizer can be used.
[0068] The protective layer can be prepared by a known method, for example, by applying a resin composition onto a release sheet and drying the same to form a protective layer, or by extruding the resin composition into a sheet using an extrusion molding machine such as a T-die.
[0069] The coating method may be a known coating method such as gravure coating, kiss coating, die coating, lip coating, comma coating, blade coating, roll coating, knife coating, spray coating, bar coating, spin coating, or dip coating. A drying step is preferably carried out during coating. For the drying step, a known drying device such as a hot air dryer or an infrared heater may be used.
[0070] The protective layer may also be a film made of an insulating resin such as polyester, polycarbonate, polyimide, polyamideimide, polyamide, polyphenylene sulfide, or polyether ether ketone.
[0071] The thickness of the protective layer before being heat-pressed is preferably 2 to 20 μm. When the protective layer has a thickness of 2 to 20 μm, both high temperature and high humidity stability and a thin electromagnetic shielding sheet can be achieved.
[0072] <<Manufacturing method of electromagnetic wave shielding sheet>> In producing the electromagnetic wave shielding sheet, a known method can be used for laminating the conductive adhesive layer and the metal layer. For example, (i) an electrolytic copper foil having a carrier material and a conductive adhesive layer formed on a release sheet (ii) a method in which a protective layer is formed on a release sheet, the protective layer is laminated on the electrolytic copper foil side of the electrolytic copper foil having a carrier material, and the electrolytic copper foil side is then laminated with a conductive adhesive layer, and the carrier material is then peeled off; (iii) a method in which a protective layer is formed on a release sheet, the protective layer is laminated on the electrolytic copper foil side of the electrolytic copper foil having a carrier material, and the carrier material is then peeled off; (iv) a method in which a conductive adhesive layer is laminated on a release sheet, the protective layer is laminated on the electrolytic copper foil side of the electrolytic copper foil having a carrier material, and the carrier material is then peeled off; (iv) a method in which a conductive adhesive layer is formed on a release sheet, the conductive adhesive layer is laminated on the electrolytic copper foil side of the carrier material-attached copper foil by coating the electrolytic copper foil side with a resin composition to form a protective layer, and a release sheet is then attached to the electrolytic copper foil side; (v) a method in which a conductive adhesive layer is formed on a release sheet, the conductive adhesive layer is laminated on the electrolytic copper foil side of the carrier material-attached copper foil by overlaying and laminating the conductive adhesive layer, and then the carrier material is peeled off; (v) a method in which a needle-shaped tool is used to form an opening in the electromagnetic shielding sheet on the release sheet; (vi) a method in which the formed protective layer is laminated on the electrolytic copper foil surface side of an electrolytic copper foil having a carrier material, and then the carrier material is peeled off, and then a conductive adhesive layer is formed on the surface from which the carrier material has been peeled off; (vi) a method in which a conductive adhesive layer is formed on a release sheet, and the surface of the rolled copper foil having an opening and the conductive adhesive layer are laminated on top of each other, and then a protective layer formed separately on a release sheet is laminated on the other surface laminated with the conductive adhesive layer; (vii) a method in which the conductive adhesive layer is formed on a release sheet and the other surface laminated with the conductive adhesive layer are laminated on top of each other; (viii) a method in which a resin composition is applied to the surface of a rolled copper foil having an opening to form a protective layer, and a release sheet is attached to the other surface of the rolled copper foil having an opening, and then a conductive adhesive layer formed on a separate release sheet is laminated on the other surface; (ix) a method in which a conductive resin composition is applied to the surface of a rolled copper foil having an opening to form a conductive adhesive layer, and a release sheet is attached to the other surface, and then a protective layer formed on a separate release sheet is laminated on the other surface; and the like.
[0073] The electromagnetic wave shielding sheet may have other functional layers in addition to the conductive adhesive layer, the metal layer, and the protective layer, which are layers having functions such as hard coat properties, water vapor barrier properties, oxygen barrier properties, thermal conductivity, low dielectric constant, high dielectric constant, or heat resistance.
[0074] The electromagnetic wave shielding sheet of the present invention can be used in various applications that require electromagnetic wave shielding. For example, it can be used in flexible printed wiring boards, rigid printed wiring boards, COF, TAB, flexible connectors, liquid crystal displays, touch panels, etc. It can also be used as a member that blocks electromagnetic waves in computer cases, building materials such as walls and window glass, vehicles, ships, aircraft, etc.
[0075] Furthermore, the electromagnetic wave shielding sheet of the present invention has excellent transmission characteristics, in which the transmission loss when a 15 GHz sine wave is applied to the signal wiring of a coplanar circuit is less than 8 dB.
[0076] Specifically, the transmission characteristics can be evaluated, for example, as follows. First, a coplanar circuit is prepared. A coplanar circuit is a type of planar transmission circuit in which signal wiring is printed on one side of an insulating substrate such as a polyimide film, and in the present invention, a coplanar circuit is used in which ground wiring is formed in parallel on a polyimide film, sandwiching two signal wirings. Note that the above-mentioned coplanar circuit has a ground pattern for grounding installed on the opposing side via a through hole. The conductive adhesive layer of the electromagnetic shielding sheet is attached to the insulating substrate surface opposite the signal wiring of the coplanar circuit, and the electromagnetic shielding sheet is laminated by heat pressing. At this time, the electromagnetic shielding sheet is conductive with the partially exposed ground pattern. By using the above-mentioned method, the transmission characteristics A test piece for evaluating the performance can be obtained.
[0077] A network analyzer is connected to the coplanar circuit of this test piece, and a sine wave of 100 MHz to 20 GHz is applied to the signal wiring of the coplanar circuit, and the input power to output power ratio is obtained, and the transmission loss can be calculated and evaluated. Note that the voltage and current ratios can be used instead of power.
[0078] In the present invention, when a 15 GHz sine wave is applied to the signal wiring of the coplanar circuit, the transmission loss is preferably less than 8 dB, more preferably less than 7.5 dB, and even more preferably less than 7 dB. By making the transmission loss less than 8 dB, a high level of reduction in transmission loss can be achieved.
[0079] When a thermoplastic resin is used as the binder resin in the conductive adhesive layer of the electromagnetic wave shielding sheet of the present invention, the thermoplastic resin exists in a solid state, and the thermoplastic resin melts when heat pressed against the wiring circuit board and solidifies again after cooling, thereby obtaining the desired adhesive strength.
[0080] In the electromagnetic wave shielding sheet of the present invention, when a thermosetting resin is used as the binder resin in the conductive adhesive layer, the thermosetting resin and curing agent contained therein are in an uncured state (B stage), and are cured by heat pressing with the wiring circuit board (C stage) to obtain a desired adhesive strength. The uncured state includes a semi-cured state in which the curing agent is partially cured.
[0081] Incidentally, the electromagnetic wave shielding sheet is generally stored with release sheets attached to the conductive adhesive layer and protective layer in order to prevent the adhesion of foreign matter.
[0082] The release sheet is a sheet obtained by subjecting a base material such as paper or plastic to a known release treatment.
[0083] <Electromagnetic shielding wiring circuit board> The electromagnetic wave shielding wired circuit board comprises an electromagnetic wave shielding layer formed from the electromagnetic wave shielding sheet of the present invention, a cover coat layer, and a wired circuit board having a circuit pattern having signal wiring and ground wiring, and an insulating substrate. The wired circuit board can be produced by having a circuit pattern having signal wiring and ground wiring on the surface of an insulating base material, forming a cover coat layer on the wired circuit board that insulates and protects the signal wiring and ground wiring and has a via on at least a portion of the ground wiring, placing the conductive adhesive layer surface of an electromagnetic wave shielding sheet on the cover coat layer, and then heat-pressing the electromagnetic wave shielding sheet to cause the conductive adhesive layer to flow into the vias and adhere to the ground wiring.
[0084] An example of the electromagnetic wave shielding wired circuit board of the present invention will be described with reference to FIG. The electromagnetic wave shielding layer 12 includes a conductive adhesive layer 1 , a metal layer 2 , and a protective layer 3 .
[0085] The cover coat layer 8 is an insulating material that covers the signal wiring of the wiring circuit board and protects it from the external environment. The cover coat layer is preferably a polyimide film with a thermosetting adhesive, a thermosetting or ultraviolet-curing solder resist, or a photosensitive coverlay film, and a photosensitive coverlay film is more preferable for fine processing. In addition, the cover coat layer is generally made of a known resin such as polyimide that has heat resistance and flexibility. The thickness of the cover coat layer is usually about 10 to 100 μm.
[0086] The circuit pattern includes ground wiring 5 for grounding and signal wiring 6 for sending electrical signals to electronic components. Both are generally formed by etching copper foil. The thickness of the film is usually about 1 to 50 μm.
[0087] The insulating substrate 9 is a support for the circuit pattern, and is preferably a flexible plastic such as polyester, polycarbonate, polyimide, polyphenylene sulfide, liquid crystal polymer, etc., and more preferably a liquid crystal polymer or polyimide. Among these, in consideration of the use of the wiring circuit board for transmitting high-frequency signals, a liquid crystal polymer having a low relative dielectric constant and dielectric loss tangent is more preferable. When the wiring circuit board is a rigid wiring board, the insulating base material is preferably made of glass epoxy. By providing such an insulating base material, the wiring circuit board can have high heat resistance.
[0088] The electromagnetic wave shielding sheet 10 and the wiring circuit board are generally heat-pressed at a temperature of about 150-190°C, a pressure of about 1-3 MPa, and for a time of about 1-60 minutes. The heat press causes the conductive adhesive layer 1 to adhere to the cover coat layer 8, and the conductive adhesive layer 1 to flow and fill the vias 11 formed in the cover coat layer 8, thereby establishing electrical continuity with the ground wiring 5. The heat press causes the thermosetting resin to react and harden, becoming the electromagnetic wave shielding layer 12. In order to accelerate the curing, post-curing may be performed at 150 to 190° C. for 30 to 90 minutes after the heat pressing.
[0089] The opening area of the via 11 is 0.8 mm 2 Less than 0.008mm is preferable. 2 By setting the above range, the area of the ground wiring can be narrowed, and the printed wiring board can be made smaller. The shape of the via is not particularly limited, and any shape such as circle, square, rectangle, triangle, or irregular shape can be used depending on the application.
[0090] It is preferable to laminate the electromagnetic shielding layers on both sides of the wiring circuit board, since this can more effectively suppress leakage of electromagnetic waves. In addition, the electromagnetic shielding layer in the electromagnetic shielding wiring circuit board of the present invention can be used as a ground circuit in addition to shielding electromagnetic waves, which allows a part of the ground circuit to be omitted, thereby reducing the area of the wiring circuit board, thereby reducing costs and allowing it to be incorporated in a narrow area inside a housing.
[0091] In addition, the signal wiring is not particularly limited, and either a single-ended circuit consisting of one signal wiring or a differential circuit consisting of two signal wiring can be used, but a differential circuit is more preferable. On the other hand, when the circuit pattern area of the wiring circuit board is limited and it is difficult to form a ground circuit in parallel, it is also possible to use an electromagnetic wave shielding layer as the ground circuit without providing a ground circuit next to the signal circuit, thereby forming a printed wiring board structure having a ground in the thickness direction.
[0092] The electromagnetic wave shielding wired circuit board of the present invention is preferably provided (mounted) in electronic devices such as liquid crystal displays, touch panels, notebook PCs, mobile phones, smartphones, tablet terminals, and the like. EXAMPLES
[0093] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the examples, "parts" and "%" refer to "parts by mass" and "% by mass", respectively. The acid value, weight average molecular weight (Mw), and glass transition temperature (Tg) of the resin, the average particle size of the conductive filler, and the DBP oil absorption of the reinforcing particles were measured by the following methods.
[0094] <<Measurement of the acid value of binder resin>> The acid value was measured in accordance with JIS K0070. Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a tetrahydrofuran / ethanol (volume ratio: tetrahydrofuran / ethanol = 2 / 1) mixture was added and dissolved. Phenolphthalein test solution was added as an indicator, and titration was performed with 0.1N alcoholic potassium hydroxide solution. The end point was when the indicator retained a pale pink color for 30 seconds. The acid value was calculated using the following formula (unit: mgKOH / g). Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution
[0095] <Measurement of weight average molecular weight (Mw) of binder resin> The weight average molecular weight (Mw) was measured using a GPC (gel permeation chromatography) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "LF-604" columns (manufactured by Showa Denko K.K.: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 ml / min and a column temperature of 40°C, and the weight average molecular weight (Mw) was determined in polystyrene equivalent.
[0096] <Glass transition temperature (Tg) of binder resin> The Tg was measured by differential scanning calorimetry ("DSC-1" manufactured by Mettler Toledo).
[0097] <Measuring the average particle size of conductive fillers> D 50 The average particle size was measured by measuring the conductive filler with a Tornado dry powder sample module using a laser diffraction / scattering particle size distribution analyzer LS13320 (manufactured by Beckman Coulter), and is the particle size at which the cumulative value in the cumulative particle size distribution is 50%. The refractive index was set to 1.6.
[0098] <Measuring the average primary particle size of reinforcing particles> The average primary particle diameter of the reinforcing particles was determined from the average value of 20 primary particles observed in an image magnified 50,000 to 1,000,000 times by a transmission electron microscope (TEM). When the particle shape of the reinforcing particles has an average aspect ratio (long axis length / short axis length) of 1.5 or more, the average primary particle diameter was determined by averaging the long axis lengths.
[0099] <DBP oil absorption measurement> The DBP oil absorption of the reinforcing particles was measured in accordance with JIS K 6217-4 using an absorption meter (Absorption Meter S-500, manufactured by Asahi Soken Co., Ltd.).
[0100] Next, the raw materials used in the examples are shown below. 《Raw materials》 Conductive filler: Composite particles (dendritic particles with 10 parts by weight of silver coated on 100 parts by weight of copper core) Average particle size D 50 : 11.0μm Fukuda Metal Foil and Powder Co., Ltd. Binder resin 1: Polyurethane urea resin with an acid value of 5 mg KOH / g, weight average molecular weight of 54,000, and Tg of -5°C (manufactured by Toyochem Co., Ltd.) Epoxy compound: "JER828" (bisphenol A type epoxy resin, epoxy equivalent = 189g / eq) manufactured by Mitsubishi Chemical Corporation Aziridine compound: "Chemithite PZ-33" manufactured by Nippon Shokubai Co., Ltd. Reinforcing particle 1: Carbon black "MA100" (average primary particle size: 24 nm, DBP oil absorption: 100 ml / 100 g) manufactured by Mitsubishi Chemical Corporation Reinforcing particles 2: Carbon black "#45L" (average primary particle size: 24 nm, DBP oil absorption: 45 ml / 100 g) manufactured by Mitsubishi Chemical Corporation Reinforcing particles 3: Carbon black "MA8" (average primary particle size: 24 nm, DBP oil absorption: 57 ml / 100 g) manufactured by Mitsubishi Chemical Corporation Reinforcing particle 4: Acetylene black "Denka Black FX-35" (average primary particle size: 23 nm, DBP oil absorption: 220 ml / 100 g) manufactured by Mitsubishi Chemical Corporation Reinforcing particle 5: Carbon nanotube "VGCF-S" (fiber diameter: 100 nm, fiber length: 10 μm, DBP oil absorption: 265 ml / 100 g) manufactured by Showa Denko Reinforcing particles 6: Carbon black "Black Peals 2000" (average primary particle size: 15 nm, DBP oil absorption: 330 ml / 100 g) manufactured by Cabot Corporation Reinforcing particle 7: Ketjenblack "Ketjenblack EC300J" (average primary particle size: 30 nm, DBP oil absorption: 360 ml / 100 g) manufactured by Lion Specialty Chemicals Reinforcing particle 8: Silica "ZEOSIL115GR" (DBP oil absorption: 180ml / 100g) manufactured by Rhodia Reinforcing particle 9: Silica "Ultrasil U360" (DBP oil absorption: 220ml / 100g) manufactured by NANOCYL Reinforcement particle 10: Lithium phosphate (Li3PO4) (DBP oil absorption: 50ml / 100g) Reinforcing particle 11: Ketjen Black "Ketjen Black EC600JD" (average primary particle size: 30 nm, DBP oil absorption: 495 ml / 100 g) manufactured by Lion Specialty Chemicals Reinforcing particle 12: Carbon nanotube "NC7000" (fiber diameter: 9.5 nm, fiber length: 1.5 μm, DBP oil absorption: 544 ml / 100 g) manufactured by NANOCYL Reinforcement particle 13: Lithium phosphate (Li3PO4) (DBP oil absorption: 10ml / 100g)
[0101] The copper foil with carrier material used is shown in Table 1. These copper foils with carrier material are copper foils having the thickness and opening rate shown in Table 1, which are obtained by forming a pattern resist layer on the copper foil formed on the carrier material and etching the copper foil to form openings. [Table 1]
[0102] <Manufacture of conductive adhesive layer 1> A container was charged with 100 parts of binder resin 1, 75 parts of conductive filler, 10 parts of epoxy compound, 0.5 parts of aziridine compound, and 1 part of reinforcing particles 1 in terms of solid content, and a mixed solvent (toluene:isopropyl alcohol=2:1 (mass ratio)) was added so that the non-volatile content concentration was 40%, and the mixture was stirred with a disperser for 10 minutes to obtain a conductive resin composition.
[0103] The conductive resin composition was applied onto a release sheet using a bar coater so that the dry thickness was 10 μm, and then dried in an electric oven at 100° C. for 2 minutes to obtain a conductive adhesive layer 1. The dry thickness was measured using an ABS Digimatic Indicator ID-CX (manufactured by Mitutoyo Corporation).
[0104] <Manufacture of conductive adhesive layers 2 to 37> Conductive adhesive layers 2 to 37 shown in Tables 2 to 6 were produced in the same manner as for conductive adhesive layer 1, except that the amount (parts by mass) of the conductive filler and the type and amount (parts by mass) of the reinforcing particles were changed.
[0105] [Example 1] 100 parts of binder resin 1, 30 parts of epoxy compound, and 7.5 parts of aziridine compound were added in terms of solid content, and stirred with a disperser for 10 minutes to obtain resin composition 1. The obtained resin composition 1 was applied to carrier-attached copper foil A1 using a bar coater so that the dry thickness was 5 μm, and dried in an electric oven at 100° C. for 2 minutes to form protective layer 1, and a weak adhesive peelable sheet was attached to protective layer 1. The dry thickness was measured with an ABS digital indicator ID-CX (manufactured by Mitutoyo Corporation).
[0106] Next, the carrier material of the copper foil A1 with carrier material was peeled off to obtain copper foil 1. By bonding the conductive adhesive layer 1 to the copper foil surface, an electromagnetic wave shielding sheet consisting of "peelable sheet / protective layer 1 / copper foil 1 / conductive adhesive layer 1 / peelable sheet" was obtained. The copper foil 1 and the conductive adhesive layer 1 were bonded at a temperature of 90°C and a pressure of 3 kgf / cm. 2 Then, they were laminated together using a thermal laminator.
[0107] [Examples 2 to 48, Comparative Examples 1 to 4] As shown in Tables 2 to 4, the electromagnetic shielding sheets of Examples 2 to 48 and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1, except that the types of the conductive adhesive layer, protective layer, and copper foil were changed. The conductive filler content and the reinforcing particle content are each the content in 100 mass % of the conductive adhesive layer.
[0108] The thickness of the metal layer, the storage modulus of the cured conductive adhesive layer, and the Young's modulus of the conductive adhesive layer were measured by the following methods.
[0109] <Measuring the thickness of the metal layer> The thickness of the metal layer was measured by the following method. The release sheet on the conductive adhesive layer side of the electromagnetic shielding sheet was peeled off, and the exposed conductive adhesive layer and polyimide film ("Kapton 200EN" manufactured by Toray DuPont Co., Ltd.) were attached together, and the sheet was heat-pressed for 30 minutes under conditions of 2 MPa and 170°C. After cutting the sheet into a size of about 5 mm in width and 5 mm in length, 0.05 g of epoxy resin (Petropoxy 154, manufactured by Maruto Co., Ltd.) was dropped onto a glass slide, and the electromagnetic shielding sheet was attached to obtain a laminate consisting of glass slide / electromagnetic shielding sheet / polyimide film. The obtained laminate was cut by ion beam irradiation from the polyimide film side using a cross-section polisher (manufactured by JEOL Ltd., SM-09010) to obtain a measurement sample of the electromagnetic shielding sheet after heat pressing.
[0110] The cross section of the obtained measurement sample was observed using a laser microscope (Keyence Corporation, VK-X100), and the thickness of the metal layer was measured from the enlarged image. The magnification was 500 to 2000 times.
[0111] <<Measurement of storage modulus of cured conductive adhesive layer>> The storage modulus of the cured conductive adhesive layer was measured by the following method. First, two coated sheets were prepared, each coated with a conductive adhesive layer on a release sheet 50 mm wide and 50 mm long. The exposed conductive adhesive layers were attached to each other and pressed at 170°C, 2.0 MPa, and 30 minutes. After thermal curing, the release sheets on the conductive adhesive layer side were peeled off to obtain a cured conductive adhesive layer. Then, the center part of the cured conductive adhesive layer was cut to a width of 5 mm and a length of 30 mm to prepare a sample. This sample was set in a dynamic viscoelasticity measuring device (Dynamic Viscoelasticity Measuring Device DVA-200, manufactured by IT Measurement and Control Co., Ltd.) and dynamic viscoelasticity measurement was performed under the conditions of a heating rate of 10°C / min, a measuring frequency of 1 Hz, and a strain of 0.08%, and the storage modulus at 85°C was read from the obtained dynamic viscoelasticity curve.
[0112] <<Measurement of Young's modulus of conductive adhesive layer>> The Young's modulus of the conductive adhesive layer was measured by the following method. First, two sheets of coated material were prepared in which a conductive adhesive layer was coated on a release sheet having a width of 50 mm and a length of 50 mm, and the exposed conductive adhesive layers were bonded together, and the release sheets on the conductive adhesive layer side of each were peeled off to obtain a conductive adhesive layer laminate. This conductive adhesive layer laminate was left to stand for 24 hours at 23°C and a relative humidity of 50%, and cut into a piece having a width of 20 mm and a length of 48 mm to prepare a sample. The stress-strain curve of this sample was measured using a tensile tester (EZ Tester, manufactured by Shimadzu Corporation), and the linear regression (slope) in the strain (elongation) range of 0.1 to 5% was taken as the Young's modulus at 23°C. (Measurement conditions: 23°C, relative humidity 50%, tensile speed 50 mm / min, and gauge length 25 mm)
[0113] The electromagnetic wave shielding sheets thus obtained were subjected to the following evaluations, and the results are shown in Tables 2 to 4.
[0114] <High temperature and high humidity stability> The high temperature and high humidity stability was evaluated by measuring the connection resistance through a small opening via. The specific evaluation method is shown below. An electromagnetic shielding sheet was prepared with a width of 20 mm and a length of 50 mm to serve as sample 25. Referring to the plan views of Figs. 7(1) and (4), the release sheet was peeled off from sample 25, and the exposed The conductive adhesive layer 25b was applied to a separately prepared flexible printed wiring board (a polyimide film 21 having a thickness of 25 μm on which copper foil circuits 22A and 22B, both of which are not electrically connected to each other and have a thickness of 18 μm, are formed, and a copper foil circuit 22B having a thickness of 37.5 μm and a diameter of 1.1 mm (via area of 1.0 mm) was formed on the copper foil circuit 22A). 2 7(3) was pressed onto a circuit board (a laminated circuit board with an adhesive-attached polyimide coverlay 23 having a circular via 24) at 170°C, 2 MPa, and 30 minutes, and the conductive adhesive layer 25b and protective layer 25a of the electromagnetic shielding sheet were cured to obtain a sample. Next, the release sheet on the protective layer 25a side of the sample was removed, and the initial connection resistance between 22A-22B shown in the plan view of Figure 7(4) was measured using a BSP probe of "Lorestar GP" manufactured by Mitsubishi Chemical Analytech. Note that Figure 7(2) is a D-D' cross-sectional view of Figure 7(1), and Figure 7(3) is a C-C' cross-sectional view of Figure 7(1). Similarly, Figure 7(5) is a D-D' cross-sectional view of Figure 7(4), and Figure 7(6) is a C-C' cross-sectional view of Figure 7(4). The sample was placed in a high-temperature, high-humidity chamber (PHP-2J, manufactured by Espec Corporation) and exposed for 500 hours under the following conditions: temperature: 85°C, relative humidity: 85%. After that, the connection resistance of the sample was measured in the same manner as the initial value. The evaluation criteria for high temperature and high humidity stability are as follows. ◎: (Connection resistance value after exposure) / (Initial connection resistance value) is less than 1.5. Extremely good. ○: (Connection resistance value after exposure) / (Initial connection resistance value) is 1.5 or more and less than 3.0. Good. △: (Connection resistance value after exposure) / (Initial connection resistance value) is 3.0 or more and less than 5.0. Practical use is possible. ×: (Connection resistance value after exposure) / (Initial connection resistance value) is 5.0 or more. Not practical use.
[0115] <Transmission characteristics> The transmission characteristics were evaluated using wiring board 21 having a coplanar circuit with an electromagnetic shielding sheet as shown in FIG.
[0116] FIG. 4 shows a schematic plan view of the main surface side of the flexible printed wiring board having a coplanar circuit (hereinafter, also referred to as a wiring board having a coplanar circuit) 20 used in the measurement, and FIG. 5 shows a schematic plan view of the back surface side. First, a double-sided CCL "R-F775" (manufactured by Panasonic Corporation) was prepared in which rolled copper foil having a thickness of 12 μm was laminated on both sides of a polyimide film 50 having a thickness of 50 μm. Then, six through holes 51 (diameter 0.1 mm) were provided near each of the four rectangular corners. Note that in the figure, only two through holes 51 are shown at each corner for convenience of illustration. Next, electroless plating was performed, and then electrolytic plating was performed to form a 10 μm copper plating film 52, and electrical continuity between the main surface and the back surface was ensured via the copper plating film formed in the through holes 51. Then, as shown in FIG. 4 , two signal wires 53, each 10 cm long, were formed on the main surface of the polyimide film 50, along with a ground wire 54 extending parallel to the signal wires 53 on the outside of the signal wires 53, and a ground pattern 55 was formed in an area extending from the ground wires 54 and including the through-holes 51 in the short direction of the polyimide film 50.
[0117] Thereafter, the copper foil formed on the back surface of the polyimide film 50 was etched to obtain a back surface ground pattern 56 as shown in FIG. 5 at a position corresponding to the ground pattern 55. The inspection specifications for the circuit appearance and tolerance were JPCA standard (JPCA-DG02). Next, a cover coat layer 8 "CISV1215 (manufactured by Nikkan Industries Co., Ltd.)" consisting of a polyimide film (thickness 12.5 μm) and an insulating adhesive layer (thickness 15 μm) was attached to the main surface side of the polyimide film 50. In addition, in FIG. 4, the cover coat layer 8 is shown in a perspective view so that the structure of the signal wiring 53 and the like can be seen. Thereafter, the copper foil pattern exposed from the cover coat layer 8 was nickel-plated (not shown) and then gold-plated (not shown).
[0118] 6, an electromagnetic wave shielding sheet 10 consisting of a laminate of a conductive adhesive layer 1, a metal layer 2, and a protective layer 3 was prepared, and a release-treated sheet (not shown) provided on the conductive adhesive layer 1 of the electromagnetic wave shielding sheet 10 was peeled off. The entire rear surface of wiring board 20 having a coplanar circuit was pressure-bonded, with adhesive layer 1 facing inward, under conditions of 170° C., 2.0 MPa, and 30 minutes to obtain wiring board 21 having a coplanar circuit with an electromagnetic shielding layer. In FIG. 6, rear surface side ground pattern 56 is shown in a see-through view.
[0119] The L / S (line / space) of the signal wiring 53 was appropriately adjusted so that the characteristic impedance was within ±10 Ω. The width of the ground wiring 54 was 100 μm, and the distance between the ground wiring 54 and the signal wiring 53 was 1 mm.
[0120] A network analyzer E5071C (manufactured by Agilent Japan) was connected to the exposed signal wiring 53 of the wiring board 20 having a coplanar circuit with an electromagnetic shielding sheet, and a 15 GHz sine wave was input to measure the transmission loss to evaluate the transmission characteristics. The measured transmission characteristics were evaluated according to the following criteria. ◎: Transmission loss at 15 GHz is less than 7.0 dB. Very good. ◯: Transmission loss at 15 GHz is 7.0 dB or more and less than 7.5 dB. Good. △: Transmission loss at 15 GHz is 7.5 dB or more and less than 8.0 dB. Practical use is possible. ×: Transmission loss at 15 GHz is 8.0 dB or more. Not practical.
[0121] <High frequency shielding> The high frequency shielding performance is measured in accordance with ASTM D4935, using a Keycom coaxial tube type shielding effect measurement system to irradiate electromagnetic waves at 100MHz to 15GHz, measure the amount of attenuation of the electromagnetic waves by the electromagnetic shielding sheet, and indicate the results according to the following standards. The measured value of the attenuation is in decibels (unit: dB). ◎: Attenuation when exposed to 15GHz electromagnetic waves is less than -55dB (extremely good). 〇: Attenuation when exposed to 15GHz electromagnetic waves is -55dB or more and less than -50dB. Good. △: Attenuation when exposed to 15GHz electromagnetic waves is -50dB or more and less than -45dB. Practical use is possible. ×: Attenuation when exposed to 15GHz electromagnetic waves is -45dB or more. Not practical.
[0122] <Solder reflow resistance> The solder reflow resistance was evaluated based on the presence or absence of change in appearance after contacting the electromagnetic shielding sheet with molten solder. An electromagnetic shielding sheet with high solder reflow resistance does not change in appearance, but an electromagnetic shielding sheet with low solder reflow resistance develops bubbles and peels off. First, the release sheet of the conductive adhesive layer of the electromagnetic shielding sheet with a width of 25 mm and a length of 70 mm was peeled off, and the exposed conductive adhesive layer and the gold-plated surface of a gold-plated copper-clad laminate with a total thickness of 64 μm (gold plating 0.3 μm / nickel plating 1 μm / copper foil 18 μm / adhesive 20 μm / polyimide film 25 μm) were pressed together at 170°C, 2.0 MPa, and 30 minutes, and then heat-cured to obtain a laminate. The obtained laminate was cut into a size of 10 mm wide and 65 mm long to prepare a sample. The obtained sample was left in an atmosphere of 40°C and 90% RH for 72 hours. After that, the sample was floated on molten solder at 250°C with the polyimide film side facing down for 1 minute, and then the sample was removed and its appearance was visually observed, and the presence or absence of abnormalities such as foaming, lifting, and peeling was evaluated according to the following criteria. ◎: No change in appearance at all. Very good. Good: A small amount of bubbles is observed. △: Many small bubbles are observed. Practical use is possible. ×: Severe foaming and peeling are observed. Not practical.
[0123] <Punching processability> The punching processability was evaluated by the method shown below. The electromagnetic shielding sheets with release films obtained in the Examples and Comparative Examples were punched out into 50 pieces of 10 mm x 30 mm using a punching machine, and the number of defective pieces was counted. The defective rate was calculated using the following formula (1) to evaluate punching workability. Formula (1) (Defective rate) = (Number of defective pieces) / (Total number of cut pieces) x 100 In addition, defective products refer to products in which part of the conductive adhesive layer protrudes from the mold after being processed into the die-cut shape, products in which the edge shape of the conductive adhesive layer is distorted, products in which burrs have occurred at the edge of the metal layer, products in which the metal layer and the conductive adhesive layer have peeled off, and products in which cracks have occurred in part of the conductive adhesive layer. ◎: Defective rate is less than 10%. Very good. ○: Defective rate is 10% or more and less than 15%. Good. △: Defective rate is between 15% and 25%. Practical use is possible. ×: Defective rate is 25% or more. Not practical.
[0124] [Table 2]
[0125] [Table 3]
[0126] [Table 4]
[0127] [Table 5]
[0128] [Table 6] [Explanation of symbols]
[0129] 1 Conductive adhesive layer 2 metal layers 3 protective layer 4 Openings 5 Ground wiring 6 Signal wiring 7. Electromagnetic shielding wiring circuit board 8 Covercoat Layer 9. Insulating substrate 10. Electromagnetic wave shielding sheet 11 Via 12 Electromagnetic Shielding Layer 20 Coplanar circuit board 21 Circuit board having coplanar circuit with electromagnetic shielding sheet 50 Polyimide film 51 Through Hole 52 Copper plating film 53 Signal wiring 54 Ground wiring 55 Grand Pattern(i) 56 Back side ground pattern (ii)
Claims
1. A laminate including a conductive adhesive layer, a metal layer, and a protective layer in this order, The conductive adhesive layer contains a binder resin, a conductive filler, and reinforcing particles, the conductive filler is a fine particle of a conductive metal selected from gold, platinum, silver, copper, and nickel, an alloy thereof, or a conductive polymer; The electromagnetic wave shielding sheet is characterized in that the reinforcing particles have a DBP oil absorption, as defined in JIS K 6217-4, of 15 to 400 ml / 100 g.
2. The conductive adhesive layer was heated at 170° C. for 30 minutes to obtain a cured conductive adhesive layer having a storage modulus of 1.0×10 at 85° C. 6 ~2.0 x 10 8 2. The method according to claim 1, wherein the temperature is 100° C. or less. Electromagnetic wave shielding sheet.
3. 3. The electromagnetic wave shielding sheet according to claim 1, wherein the conductive adhesive layer has a Young's modulus at 23° C. of 10 to 450 MPa.
4. 4. The electromagnetic shielding sheet according to claim 1, wherein the content of the reinforcing particles is 1 to 20 mass % relative to 100 mass % of the conductive adhesive layer.
5. 5. The electromagnetic shielding sheet according to claim 1, wherein the reinforcing particles are carbon black.
6. 6. The electromagnetic shielding sheet according to claim 1, wherein the conductive filler has a content of 25 to 90 mass % relative to 100 mass % of the conductive adhesive layer.
7. 7. The electromagnetic shielding sheet according to claim 1, wherein the metal layer has a plurality of openings, the opening ratio being 0.1 to 20%.
8. 8. The electromagnetic wave shielding sheet according to claim 1, wherein the metal layer has a thickness of 0.3 to 7 μm.
9. 9. An electromagnetic wave shielding wiring circuit board comprising an electromagnetic wave shielding layer formed from the electromagnetic wave shielding sheet according to any one of claims 1 to 8, a cover coat layer, and a wiring board having signal wiring and an insulating substrate.
Citation Information
Patent Citations
Heat-conductive electromagnetic wave shield sheet
JP2000124660A
Composite filter for display device
JP2010010461A
Electromagnetic wave shield sheet and manufacturing method of wiring board with electromagnetic wave shield layer
JP2013168643A
Electromagnetic wave shield film, flexible printed wiring board with electromagnetic wave shield film, electronic equipment, and method for manufacturing the same
JP2015015304A
Electromagnetic wave shield film and printed wiring board
JP2017135248A